Outcomes of surgery for benign and malignant adrenal disease from the British Association of Endocrine and Thyroid Surgeons' national registry. Issue 11 (19th August 2019) - Patel, N.; Egan, R. J.; Carter, B. R.; Scott‐Coombes, D. M.; Stechman, M. J.
Abstract : Background: This study investigated the indications, procedures and outcomes for adrenal surgery from the UK Registry of Endocrine and Thyroid Surgery database from 2005 to 2017, and compared outcomes between benign and malignant disease. Methods: Data on adrenalectomies were extracted from a national surgeon‐reported registry. Preoperative diagnosis, surgical technique, length of hospital stay, morbidity and in‐hospital mortality were examined. Results: Some 3994 adrenalectomies were registered among patients with a median age of 54 (i.q.r. 43–65) years (55·9 per cent female). Surgery was performed for benign disease in 81·5 per cent. Tumour size was significantly greater in malignant disease: 60 (i.q.r. 34–100) versus 40 (24–55) mm ( P < 0·001). A minimally invasive approach was employed in 90·2 per cent of operations for benign disease and 48·2 per cent for cancer ( P < 0·001). The conversion rate was 3·5‐fold higher in malignant disease (17·3 versus 4·7 per cent; P < 0·001). The length of hospital stay was 3 (i.q.r. 2–5) days for benign disease and 5 (3–8) days for malignant disease ( P < 0·050). In multivariable analysis, risk factors for morbidity were malignant disease (odds ratio (OR) 1·69, 1·22 to 2·36; P = 0·002), tumour size larger than 60 mm (OR 1·43, 1·04 to 1·98; P = 0·028) and conversion to open surgery (OR 3·48, 2·16 to 5·61; P < 0·001). The in‐hospital mortality rate was below 0·5 per cent overall, but significantly higher in the setting of malignant disease (1·2 versus 0·2 per cent; P < 0·001). Malignant disease (OR 4·88, 1·17 to 20·34; P = 0·029) and tumour size (OR 7·47, 1·52 to 39·61; P = 0·014) were independently associated with mortality in multivariable analysis. Conclusion: Adrenalectomy is a safe procedure but the higher incidence of open surgery for malignant disease appears to influence postoperative outcomes. Abstract : This article examined the incidence of recorded benign and malignant adrenal surgery per year. Low rate of complications Abstract : Antecedentes: Este estudio investigó las indicaciones, procedimientos y resultados de la cirugía de la glándula suprarrenal a partir de la base de datos de la UKRETS desde 2005‐2017 y comparó los resultados entre enfermedad benigna y maligna. Métodos: Se examinó un registro nacional con datos notificados por cirujanos que incluye 3.994 suprarrenalectomías; 57% mujeres, mediana de edad 53 (8‐88 años). Se evaluaron el diagnóstico preoperatorio, la técnica quirúrgica, la duración de la estancia hospitalaria, la morbilidad y la mortalidad hospitalaria. Resultados: En el 82% de los casos la cirugía se realizó por enfermedad benigna. El tamaño del tumor fue significativamente mayor en la enfermedad maligna: 60 mm (34‐100 mm) versus 40 mm (24‐55 mm), P < 0, 001. Se utilizó un abordaje mínimamente invasivo en el 90% de los casos de enfermedad benigna y en el 48% de las operaciones por cáncer ( P < 0, 001). La tasa de conversión fue 3, 5 veces más alta en la enfermedad maligna (17% versus 4, 9%, P < 0, 001). La duración de la estancia fue 3 días (rango intercuartílico, interquartile range, IQR 2‐5) para la enfermedad benigna y 5 (IQR 3‐8) días para la enfermedad maligna ( P < 0, 05). En el análisis multivariable, los factores de riesgo para la morbilidad fueron: enfermedad maligna (razón de oportunidades, odds ratio, OR 1, 64, 1, 217‐2, 359; P = 0, 002), tamaño del tumor (OR 1, 433, 1.040‐1, 967; P = 0, 028) y conversión a cirugía abierta (OR 3, 483, 2, 160‐5, 612; P < 0, 0001). La mortalidad hospitalaria global fue baja (< 0, 5%) pero significativamente mayor en el escenario de la enfermedad maligna (1, 2% versus 0, 2%, P < 0, 001). La enfermedad maligna (OR 4, 881, 1, 171‐20, 343; P = 0, 029) y el tamaño del tumor (OR 7, 474, 1, 515‐39, 610; P = 0, 014) se asociaron de forma independiente con la mortalidad en el análisis multivariable. Conclusión: La suprarrenalectomía es un procedimiento seguro, pero la mayor incidencia de cirugía abierta para la enfermedad maligna parece tener un impacto sobre los resultados postoperatorios.